Acquisition Dynamics of Borrelia duttonii by Ornithodoros moubata over time - Hurbean, Beatrice (Jihočeská univerzita, 2022)
The aim of the thesis is to identify the transmission and acquisition dynamics of Borrelia duttonii by Ornithodoros moubata under normal as well as extreme conditions. Additionally, the infectivity of B.duttonii from brain tissue is tested to confirm data reporting on B.duttonii leaving a residual infection in the brains of mice.
Acquisition Dynamics of Borrelia duttonii by Ornithodoros moubata over time
Keywords: Disease; Bacteria; Borrelia; Borrelia duttonii; Soft ticks; Ticks; Argaside; Ornithodoros moubata; Acquisition dynamics; Residual brain infection; Transmission; Disease; Bacteria; Borrelia; Borrelia duttonii; Soft ticks; Ticks; Argaside; Ornithodoros moubata; Acquisition dynamics; Residual brain infection; Transmission